Influence of behavioural implication of information on the selection of accounting methods and their reflection on investor's decisions field study on Iraq stock exchange - Hussein AL-Aameri, Omar Ali; H. Yahiya Al-Temimi, Abbas (Journal of Economics and Administrative Sciences, 2020)
The research aims to highlight on the behavioural approach in accounting, and clarify the behavioural implications of the main activities of accounting, and clarify the concept of information inductance within the framework of the behavioural approach and its impact on preparing financial statements. And that the impact of financial information on the behaviour of investment decision-makers, and to achieve the goals of the research, the researcher prepared a questionnaire according to Likert five-step scale, and he took into consideration in preparing it in line with the characteristics of the study community, and that the target community for this questionnaire is the investors in the Iraq Stock Exchange. The researcher reached a set of conclusions and recommendations, and the most important conclusions are the following: There is a significant effect of the behavioural implications of information on the selection of accounting methods, and There is a significant effect of the accounting methods on the investors ’decisions with the presence of the behavioural implications of the information, and If the accountant anticipates the results of using the information, he may lead it and before communicating any information, and therefore even before any results appear, he chooses to change the information, his behaviour or even his goals, and It is possible to predict the behaviour of individuals and guide this behaviour in an appropriate way by providing the appropriate information in the decision-making process, and By being aware of the users ’reactions to the accounting methods, the accountant can use the preferred alternative accounting methods for them. Either the most important recommendations are: The need to take account of the preparers of accounting information behavioural aspects, and take the reaction of users to accounting information in consideration when performing accounting work, and choose accounting methods, and The need to pay attention to the information provided to investors, which helps them in making investment decisions, and to provide this information periodically and systematically and provide it with the speed and accuracy possible, and work to provide the appropriate information in terms of quantity, type and time in order to facilitate proper investment decision-making